Exogenous application of growth regulators improves the growth and quality of Dahlia variabilis L. - Khan, Shahbaz (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2023)
Dahlia (Dahlia variabilis L.), a bulb crop sold as cut flower, garden ornamental/potted plant, becomes a popular cut flower in the world. This experiment was designed to study the effects of foliar applied gibberellic acid, zinc, ascorbic acid, and thiamine on the growth and flower attributes of dahlia. The study was conducted under greenhouse conditions at the Floriculture Research Area, University of Agriculture, Faisalabad, Pakistan. There were thirteen treatment with three levels each; gibberellic acid, zinc sulphate, ascorbic acid, and thiamine. First, foliar application was done at vegetative stage (after 45 d of transplantation) and second, at the flowering stage. Application of gibberellic acid at 100 ppm significantly improved plant height (92.67 cm). Application of zinc at 0.50% produced the maximum number of flowers (28.47), diameter of flower (100.19 mm), and fresh weight of flower (11.16 g). Foliar application of thiamine increased nutrient accumulation in leaves of dahlia. The nitrogen contents (4.43 %) increased to maximum in response to treatment comprising ascorbic acid, whereas phosphorus content (1.41 mg g-1) and potassium contents (19.45 mg g-1) were at maximum in response to thiamine. The highest chlorophyll a (4.37 mg g-1) and b (2.04 mg g-1) contents were recorded in treatment comprising thiamine at 150 ppm. The highest carbohydrate contents (35.14%) were recorded in zinc application response. Application of thiamine significantly reduced the days of flowering and flower diameter. Overall, it can be recommended that application of thiamine at 150 ppm is more responsive to improve the growth and quality of dahlia flower as compared to gibberellic acid, zinc, and ascorbic acid.